2020
DOI: 10.1111/1759-7714.13645
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between CXCR4, CXCR5 and CCR7 expression and survival outcomes in patients with clinical T1N0M0 non‐small cell lung cancer

Abstract: Background: Lung cancer is the leading cause of cancer-related death. Even if early detection and treatment have proven to be effective, the survival outcomes are still poor. Methods: Tissue samples and clinicopathological data of 244 patients with clinical T1N0M0 NSCLC were collected. We investigated CXCR4, CXCR5 and CCR7 expression levels using the immunohistochemical method and analyzed their correlations with clinicopathological characteristics and survival outcomes. Results: Elevated expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Enhanced expression levels of CXCR4, CXCR5 and CCR7 were found in tumor tissues compared to normal tissue. Moreover, 5 year disease-free survival and 5 year overall survival were significantly higher for lung cancer patients with positive expression for all three chemokine receptors compared to controls with CCR7 expression having the highest significance ( p < 0.001 for both survival parameters) [ 220 ]. It is not obvious why these two studies buck the trend and suggest that CCR7 is the good guy; however, a recent bioinformatics study looked at various chemokine receptor expression patterns, including CCR7 expression, in relation to NSCLC stage compared to normal tissue and reported that CCR7 was expressed at all stages with higher expression in early stages that tails off as the tumor progresses [ 221 ].…”
Section: Tumors Of Surface Epitheliamentioning
confidence: 99%
“…Enhanced expression levels of CXCR4, CXCR5 and CCR7 were found in tumor tissues compared to normal tissue. Moreover, 5 year disease-free survival and 5 year overall survival were significantly higher for lung cancer patients with positive expression for all three chemokine receptors compared to controls with CCR7 expression having the highest significance ( p < 0.001 for both survival parameters) [ 220 ]. It is not obvious why these two studies buck the trend and suggest that CCR7 is the good guy; however, a recent bioinformatics study looked at various chemokine receptor expression patterns, including CCR7 expression, in relation to NSCLC stage compared to normal tissue and reported that CCR7 was expressed at all stages with higher expression in early stages that tails off as the tumor progresses [ 221 ].…”
Section: Tumors Of Surface Epitheliamentioning
confidence: 99%
“…Previous studies have shown that CXCR4 is highly expressed in NSCLC and is related to the prognosis of patients [ 21 ]; however, the same in both the LUAD and LUSC subgroups has not been shown before. We confirmed the prognostic value of CXCR4 in LUAD and LUSC patients based on an independent cohort—high CXCR4 expression predicts poor patient prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…However, the potential of CXCR4 as a tumor immune prognostic marker has not been extensively studied, especially in NSCLC. To the best of our knowledge, the prognostic value of CXCR4 in NSCLC has been assessed in small-scale samples [ 21 ] but the relationship between CXCR4 and immune markers has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…CXCR5 + CD8 T cells correlate with disease-free or overall survival in pancreatic, colon, follicular lymphoma, gastric, high-grade serous ovarian, hepatocellular, and bladder cancers and thus is considered a potential biomarker ( 15 , 17 , 20 , 23 , 25 , 26 ). On the contrary, decreases in disease-free survival in non-small cell lung and salivary adenoid cystic carcinomas are associated with infiltrating CXCR5 + CD8 T cells ( 74 , 75 ). Functional studies beyond correlative data and mRNA expression remains lacking as to how these cells benefit or negate a tumor microenvironment.…”
Section: Could Cxcr5 + Cd8 T Cells Initiate the De...mentioning
confidence: 99%